IMPLEMENTASI NILAI-NILAI DAKWAH SANTRI MELALUI PERIBAHASA ARAB MAHFUDZAT - Andi Fajar Awaluddin (fakultas Ushuluddin dan Dakwah IAIN Bone, 2020)
AbstractDa'wah activities in a plurality society not only have a strong basic principles of faith but can also realize basic principles of moral and social ethics. Their existence must receive guidance so that the community has the character of loving kindness, opposing evil, and not recognizing violence in accordance with Islamic teachings. Under these conditions, a strong foundation of faith will be able to realize a life that is in harmony with everyday life such as a sense of social justice, security, mutual assistance to help, respect, and others. The values of da'wah mentioned above must be implemented in everyday life in a plurality society with reference to the principles, namely : (1) Islamic civilization stand son the basis of monotheism,(2) civilization that is humane, transcendental, and has international insight, (3) always hold moral principles. Keywords : The values of da’wah, Proverb, Mahfudzat